Green HRM: Strategies for Sustainable Business Practices and Employee Engagement - Palupiningtyas, Dyah (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research investigates the relationship between the implementation of Sustainable Human Resource Management (Green HRM) practices, employee engagement, and organizational performance in the context of environmental sustainability. Through this study, we identified factors influencing the implementation of Green HRM, including the use of renewable energy, environmentally friendly employee selection policies, training on sustainable practices, and reducing the use of paper and plastic in the workplace. We find that the implementation of Green HRM practices contributes positively to employee engagement, which in turn improves organizational performance. Employee engagement plays a significant mediating role in linking Green HRM practices with organizational performance. The managerial implication of this research is the importance of designing Green HRM strategies that strengthen employee involvement and ensure alignment with organizational goals to improve overall performance. This research makes an important contribution to our understanding of the relationship between Green HRM, employee engagement, and organizational performance in the context of sustainability.